Double Fatherless: Bias Gender Tak-Sadar, Kelangkaan Guru Laki-laki di TK, dan Keadilan Sosial Dalam Pendidikan Indonesia - Yuliati, Ni Komang Dwi Eka; Sriartha, I Putu; Mudana, Wayan; Pageh, I Made (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study analyzes the phenomenon of "double fatherless" as a manifestation of unconscious gender bias in the Indonesian education system, focusing on the absence of male figures in both family and school contexts. Through literature review, analysis of training documents (INOVASI), and examination of empirical cases, the research identifies that unconscious bias against men results in stigmatization of male teachers in early childhood education while simultaneously creating a double burden for women who bear both domestic and public roles. This study connects this global phenomenon to local Indonesian context, particularly the nyentana practice in Tabanan Bali which displays gender ambivalence: strengthening women's position as heirs while multiplying their social responsibilities. Using frameworks of relational justice (Nancy Fraser and John Rawls) and critical education theory (Paulo Freire, John Dewey), the research proposes a reorientation of education that accommodates not only gender equality in a narrow sense, but also recognition of male vulnerability and complexity of gender relations in multiethnic Indonesian contexts. Research findings indicate the need for teacher training based on critical awareness of symmetrical gender bias, gender-sensitive curriculum accommodating non-mainstream families, and inclusive policies that position men in caregiving roles without stigma. Practical implications include redesigned teacher training, reform of recruitment policies, research on student resilience in gender-responsive family and school contexts, and important implications for early grade reading literacy development.